Exploration of assistive technology transforming lives, March 15 - Archive, FSN::::::::: (2013)
The Friends of the Madden Library will present, 'Technology and Human Mobility: From Disabled to Enabled,' the fourth program in The Friends of the Madden Library's 2012/13 season themed Technology and Culture: Progress or Peril.